Application of the Index Card Match Strategy to Improve Students' Mathematical Problem Solving Ability - Winda Khadijah Ashareni Tanjung (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to find out how to increase the ability to solve mathematical problems through the application of Index Card Match learning strategies. The subjects in this study were 16 students in class IX A at Karya Bunda Mandiri Middle School. This research is a classroom action research (PTK) which consists of 2 cycles, each cycle consisting of 2 meetings. The results of the problem solving ability test increased from the initial test, cycle I and cycle II. In the classical pre-test 4 students (25%) passed and the average pre-test ability was 49.4 with a very low level of ability. In the first cycle, there was an increase classically, 7 students (43.75%) completed and the average ability test was obtained 61.2 with a low level of ability. Then in the second cycle test experienced an increase classically 14 students (87.5%) completed and the average ability was obtained 78.7 with a moderate level of ability. Thus it can be concluded that the application of the Index Card Match learning strategy can improve students' problem solving abilities.